Working hours and depressive symptomatology among full-time employees: Results from the fourth Korean National Health and Nutrition Examination Survey (2007–2009) - Kim, Inah; Kim, Hyunjoo; Lim, Sinye; Lee, Mira; Bahk, Jinwook; June, Kyung Ja; Kim, Soyeon; Chang, Won Joon (Scandinavian Journal of Work, Environment & Health, 2013)
' ' OBJECTIVE ': 'This study aimed to examine the distribution of working hours and the association between working hours and depressive symptomatology using representative data from a national, population-based survey. ' ' METHOD ': 'Data came from the fourth Korean National Health and Nutrition Examination Survey (2007–2009), which employed a systematic, stratified cluster-sampling method. We used logistic regression procedures to estimate the importance of weekly working hours as a predictor of depressive symptomatology. ' ' RESULTS ': 'The prevalence of depressive symptomatology was 10.2%. The work week, which averaged 48.3 hours for the sample as a whole, was longer for men (49.8 hours) than women (45.3 hours), and 12.1% of respondents were engaged in shift work. In logistic regression analyses, compared to those working <52 hours per week, the odds ratios (OR) of working hours as a predictor of depressive symptomatology were 1.19 [95% confidence interval (95% CI) 0.77–1.85] for those working 52–59 hours per week and 1.62 (95% CI 1.20–2.18) for those working ≥60 hours per week, after adjustment for demographic characteristics, health behaviors, socioeconomic status, employment status, and work schedules. It showed a positive dose–response relationship between working hours and depressive symptomatology (P=0.0059). ' ' CONCLUSIONS ': 'Working hours in Korea are long. There is an association between working hours and depressive symptomatology, and there seems be a trend in working hours and depressive symptomatology.
Keywords: depression; depressive symptomatology; full-time employee; Korea; Korean National Health and Nutrition Examination Survey; mental disorder; mental health; mental illness; workhour; working hour; worktime